Robotic assisted-bronchoscopy: technical tips and lessons learned from the initial experience with sampling peripheral lung lesions - Murgu, Septimiu Dan (BMC Pulm Med, 2019)
BACKGROUND: Peripheral pulmonary nodules are increasingly detected in patients screened for lung cancer or during disease progression of thoracic or extrathoracic malignancies. Sampling these lesions requires surgery, computed tomography (CT)-guided biopsy or bronchoscopic interventions. Bronchoscopic interventions are preferable because they have lower complications and often patients may not be ideal candidates for surgical or CT-guided biopsy. In addition, guidelines recommend diagnosis and staging in one single procedure. The diagnostic yield of existing advanced bronchoscopic techniques including electromagnetic navigation, radial probe ultrasonography, ultrathin bronchoscopy or virtual bronchoscopy remains suboptimal. The purpose of this paper is to codify the technique whereby a diagnostic bronchoscopy is performed using the new robotic platform. METHODS: In the present report, I describe the technique for performing robotic-assisted bronchoscopy (RAB) using the Monarch™ platform (Auris Health, Inc., Redwood City, CA). RESULTS: Appropriate team training, patient selection, anesthesia settings, optimal tissue acquisition and processing, and prevention of complications are described and illustrated. CONCLUSIONS: RAB may be beneficial for patients with peripheral lung lesions that require biopsy prior to surgical resection, stereotactic radiation, targeted or immunotherapy.